Optimization operation method for hydrogen-compressed natural gas-integrated energy systems considering hydrogen-thermal multi-energy inertia - Jing Chen; Haozeng Bie; Juntao Wang; Bo Sun (Results in Engineering)
Hydrogen-enriched compressed natural gas (HCNG) holds significant promise for renewable energy absorption and hydrogen utilization, while also increasing the complexity of Integrated Energy System (IES) structures, which presents challenges for optimal HCNG-IES operation. Energy inertia provides IES with potential operational flexibility. However, existing HCNG-IES optimization technologies inadequately account for hydrogen and thermal inertia, leaving significant opportunities to enhance system performance. In this study, we begin with a comprehensive analysis and modeling of the hydrogen-thermal multi-energy inertia (HTMEI) processes, which encompass the hydrogen inertia of HCNG loads and hydrogen storage tanks, as well as the thermal inertia of thermal storage tanks and buildings. Following this, we develop an optimization model for the operation of HCNG-IES that incorporates HTMEI, to optimize the system's overall performance in terms of economic, environmental, and energy efficiency criteria. The resulting optimal scheduling scheme integrates the outputs of energy devices and multi-energy inertia processes. Case studies validate the efficacy of the proposed operational optimization method. The results indicate that, in comparison with an operational optimization method that does not consider energy inertia, the proposed approach reduces operational costs by 34.79 %, carbon emissions by 32.93 %, electricity purchased from the grid by 95.37 %, and natural gas consumption by 11.8 %. Furthermore, the analysis has verified the mutual enhancement between hydrogen inertia and thermal inertia, along with their positive individual impacts on operational performance of the HCNG-IES.